2020
DOI: 10.1002/brb3.1604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mindfulness meditation protocol in subjects with various psychometric characteristics at high altitude

Abstract: Introduction Incidence of high altitude‐related sickness is increasing due to more number of people visiting the areas of high altitude which may result in life‐threatening conditions including acute mountain sickness (AMS), high altitude pulmonary edema (HAPE), high altitude cerebral edema (HACE), and High‐altitude pulmonary hypertension (HAPH). We hypothesized that an advanced yoga regimen may be beneficial in dealing with the physiology of acclimatization. Methods Anthropometric, Biochemical, and Psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Presentations from Dr Mitali Mukherjee from the Institute of Genomics and Biotechnology, New Delhi, added a new dimension by integrating the Ayurvedic principles as means to cope up with the COVID situation. 54 , 55 This was further complemented by her colleague Dr Bhavana, who explained the role of Ayurveda in the management of fever in novel SARS-CoV-2 infection. 56 The genetic dimension to the practice of integrative health care was provided by Dr K. Thangaraj, a Chief Scientist at Centre for Cellular and Molecular Biology, Hyderabad, who gave a compelling presentation on the contemporary science correlates of Ayurveda Prakriti explaining the importance of Ayurvedic method of treatment in terminologies of traditional medicine and its scientific practices 57 prescribing the value of Integrative medicine.…”
Section: Yoga and Meditation For Mental Health And Immunity During Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…Presentations from Dr Mitali Mukherjee from the Institute of Genomics and Biotechnology, New Delhi, added a new dimension by integrating the Ayurvedic principles as means to cope up with the COVID situation. 54 , 55 This was further complemented by her colleague Dr Bhavana, who explained the role of Ayurveda in the management of fever in novel SARS-CoV-2 infection. 56 The genetic dimension to the practice of integrative health care was provided by Dr K. Thangaraj, a Chief Scientist at Centre for Cellular and Molecular Biology, Hyderabad, who gave a compelling presentation on the contemporary science correlates of Ayurveda Prakriti explaining the importance of Ayurvedic method of treatment in terminologies of traditional medicine and its scientific practices 57 prescribing the value of Integrative medicine.…”
Section: Yoga and Meditation For Mental Health And Immunity During Co...mentioning
confidence: 99%
“…Our studies show that yoga and meditation can be an effective intervention to achieve positive mental health among individuals with co-morbidities and/or lifestyle disorders. 23 , 24 The Ministry of Ayurveda, Yoga, Naturopathy, Unani, Siddha and Homeopathy (AYUSH), Government of India, has also been propagating the use of validated yoga and meditation protocols in Type 2 Diabetes Mellitus (T2DM) individuals with the goal of COVID risk reduction. 25 , 26 In addition, we have also shown improvement in the happiness index and psychosocial health using advanced meditation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported beneficial effect of meditation on adaptation to the hypoxic high altitude conditions that requires synergistic functioning of respiratory, cardiac, and hematological system. [ 83 ] The authors reported increase in the partial pressure of oxygen, (PO2) a marker of bio-availability of oxygen at the cellular levels. [ 83 ]…”
Section: Findings Of Meditation or Exercise For Preventing Acute Respmentioning
confidence: 99%
“…[ 83 ] The authors reported increase in the partial pressure of oxygen, (PO2) a marker of bio-availability of oxygen at the cellular levels. [ 83 ]…”
Section: Findings Of Meditation or Exercise For Preventing Acute Respmentioning
confidence: 99%